2006
DOI: 10.1002/jemt.20363
|View full text |Cite
|
Sign up to set email alerts
|

MRT letter: High speed scanning has the potential to increase fluorescence yield and to reduce photobleaching

Abstract: True confocal microscopy requires point-shaped illumination and detection. To generate an image, a diffraction limited spot is moved over the sample. Single spot scanning has suffered in the past from low image rates; a solution is the employment of very fast scanning devices (resonant scanners) for x-movement. In the process of introducing resonant scanning devices, it was found that both signal yield is improved and bleaching is decreased-in contrary to the assumed performance. This article will show by a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 6 publications
2
33
0
Order By: Relevance
“…While this shorter procedure proved functional for several immunostaining [22][23][24] , we found that it attenuates the robustness of the staining across samples, antibody and batch of cell wall digestion enzyme mix (see below). Furthermore we were not successful for FISH hybridization with this short procedure.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…While this shorter procedure proved functional for several immunostaining [22][23][24] , we found that it attenuates the robustness of the staining across samples, antibody and batch of cell wall digestion enzyme mix (see below). Furthermore we were not successful for FISH hybridization with this short procedure.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, we successfully used this protocol to quantitatively analyze chromatin dynamics by immunostaining in megaspore mother cells, functional megaspore, developing female gametophytes and early embryo 21,[22][23][24] . In Figure 5, we show representative results of whole-mount immunostaining on Arabidopsis ovules.…”
Section: Representative Resultsmentioning
confidence: 99%
“…The period and duty cycle of the outer pulse is highly variable. The units of the outer pulse is in 1/10 000 s/unit, and the PwM intensity varies between 0-800. reduce photo-toxicity 38,[40][41][42] while maintaining image quality. Compared with continuous wave (CW) illumination, shorter pulse widths reduced illumination and the time lag between two pulses allows all excited molecules to non-radiatively relax to the ground states via non-radiative and intermolecular (i.e., conduction and convection) as well as radiative (i.e., flourescence and phosphorecence) de-excitation processes.…”
Section: Sourcesmentioning
confidence: 99%
“…Recent developments in STED microscopy include: 1) the usage of resonant scanning mirrors that allow fast scanning (Moneron et al 2010;Westphal et al 2007) and thus, decrease the rate of fluorophore photobleaching due to triplet states buildup (Borlinghaus 2006;Tsien and Bacskai 1995); and 2) the implementation of time-gated detection with low-power continuous wave (CW) depletion lasers that reach a resolution of ~60–70 nm in biological samples (Vicidomini et al 2011;Vicidomini et al 2013). Yet, the speed of the photon counting systems limits the linear scanning speed that can be used with resonant mirrors in STED microscopes.…”
Section: Introductionmentioning
confidence: 99%